Antidiabetic, Anticoagulant, Anticholinesterase Inhibition, Anti-Tyrosinase and Anti-Inflammatory Activity of Three selected Seaweeds after Eradication of Phycocolloids from Vedalai - R.CHARU DEEPIKA (International Journal of Pharma and Bio Sciences, 2018)
The biopotentials of seaweed waste generated from industries include anticholinesterase inhibition property, anti-inflammatory, tyrosinase inhibition property, antidiabetic and anticoagulant activity. The emergence of type 2 diabetes mellitus as the pre-eminent global non-infectious disease has driven the search for new anti-diabetic strategies including utilizing traditional food and herbs. In this investigation, we describe the anti-diabetic potential of six selected Malaysian seaweed species against recognized pharmacological targets. Hyaluronidase inhibition assay was performed for accomplishment of anti-inflammatory activity while the antidiabetic activity was studied by amylase inhibition assay using chromogenic DNSA method followed by tyrosinase inhibitory assay and anticholinesterase inhibitory assay. The anticoagulant activity was evaluated from activated partial thromboplastin time. Ethanolic extracts of Sargassum wightii, Gracilaria corticata and Kappaphycus alvarezii possessed potent inhibitory activities against α-amylase. The highest inhibitory activity against α-amylase was found in ethanolic extracts of the red seaweed species Kappaphycus alvarezii after carrageenan extraction. The activated partial thromboplastin time (APTT) test was applied using normal human plasma and standard heparin (HEP) to determine the anticoagulant activity of seaweeds.